Distinct Macrophage Fates after in vitro Infection with Different Species of Leishmania: Induction of Apoptosis by Leishmania (Leishmania) amazonensis, but Not by Leishmania (Viannia) guyanensis. - Jarina Pena DaMata; Bárbara Pinheiro Mendes; Kátia Maciel-Lima; Cristiane Alves Silva Menezes; Walderez Ornelas Dutra; Lirlândia Pires Sousa; Maria Fátima Horta (PLoS ONE, 2015)
Leishmania is an intracellular parasite in vertebrate hosts, including man. During infection, amastigotes replicate inside macrophages and are transmitted to healthy cells, leading to amplification of the infection. Although transfer of amastigotes from infected to healthy cells is a crucial step that may shape the outcome of the infection, it is not fully understood. Here we compare L. amazonensis and L. guyanensis infection in C57BL/6 and BALB/c mice and investigate the fate of macrophages when infected with these species of Leishmania in vitro. As previously shown, infection of mice results in distinct outcomes: L. amazonensis causes a chronic infection in both strains of mice (although milder in C57BL/6), whereas L. guyanensis does not cause them disease. In vitro, infection is persistent in L. amazonensis-infected macrophages whereas L. guyanensis growth is controlled by host cells from both strains of mice. We demonstrate that, in vitro, L. amazonensis induces apoptosis of both C57BL/6 and BALB/c macrophages, characterized by PS exposure, DNA cleavage into nucleosomal size fragments, and consequent hypodiploidy. None of these signs were seen in macrophages infected with L. guyanensis, which seem to die through necrosis, as indicated by increased PI-, but not Annexin V-, positive cells. L. amazonensis-induced macrophage apoptosis was associated to activation of caspases-3, -8 and -9 in both strains of mice. Considering these two species of Leishmania and strains of mice, macrophage apoptosis, induced at the initial moments of infection, correlates with chronic infection, regardless of its severity. We present evidence suggestive that macrophages phagocytize L. amazonensis-infected cells, which has not been verified so far. The ingestion of apoptotic infected macrophages by healthy macrophages could be a way of amastigote spreading, leading to the establishment of infection.